IOS (INVESTMENT OPPORTUNITY SET) SEBAGAI VARIABEL UTAMA PENINGKATAN NILAI PERUSAHAAN - Farros Abyan Al Malik; Ana Kadarningsih (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to see the influence of Good Corporate Governance (GCG) which is proxied by the Independent Board of Commissioners (DKI), Return on Equity (ROE), Investment Opportunity Set (IOS) which is proxied by the Market to Book Value of Equity (MBVE). to Corporate Value (PBV). The object of this research is 154 secondary data from the Indonesian Stock Exchange (IDX), but there are only 143 data because the normality of the data does not reach 0.05. The method of data analysis in this study is descriptive analysis, data normality test. The tool or application used to analyze the data in this study is SPSS v.24 software. The results of this study indicate that the GCG variable proxied by the Independent Board of Commissioners has no significant effect on PBV, the ROE variable has no significant effect on PBV, the IOS variable has a significant positive effect on PBV.